Expression of gene region encoding pre-membrane and envelope antigen of dengu virus type 4 in Pichia pastoris - Hồng, Lê Thị Thu; Nguyệt, Phùng Thu; Hường, Trần Thị; Thanh, Nguyễn Hồng; Hồng, Phạm Thúy; Kháng, Đinh Duy; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 39-44, 2005